Expanding the role of bitter taste receptor in extra oral tissues: TAS2R38 is expressed in human adipocytes. (1st January 2020) - Cancello, Raffaella; Micheletto, Giancarlo; Meta, Dorela; Lavagno, Rosalia; Bevilacqua, Emanuele; Panizzo, Valerio; Invitti, Cecilia
ABSTRACT: Increasing evidence indicates that taste receptors mediate a variety of functions in extra-oral tissues. The present study investigated the expression of bitter taste receptor TAS2R38 in human adipocytes, the possible link with genetic background and the role of TAS2R38 in cell delipidation and lipid accumulation rate in vitro . Subcutaneous (SAT) and visceral (VAT) adipose tissues were collected in 32 obese and 18 lean subjects. The TAS2R38 gene expression and protein content were examined in whole tissues, differentiated adipocytes and stroma-vascular fraction cells (SVF). The P49A SNP of TAS2R38 gene was determined in each collected sample. The effect of two bitter agonists (6-n-propylthiouracil and quinine) was tested. TAS2R38 mRNA was more expressed in SAT and VAT of obese than lean subjects and the expression/protein content was greater in mature adipocytes. The expression levels were not linked to P49A variants. In in vitro differentiated adipocytes, bitter agonists induced a significant delipidation. Incubation with 6-n-propylthiouracil induced an inhibition of lipid accumulation rate together with an increase in TAS2R38 and a decrease in genes involved in adipocyte differentiation. In conclusion, TAS2R38 is more expressed in adipocytes of obese than lean subjects and is involved in differentiation and delipidation processes.